Considering the potential unintended consequences of RateMDs: an exploratory study in one specialty - Kristina H Pulkki; Shamira Pira; Meredith Young; Grace M Scott; Carol Nhan; Kevin Fung; Gabriella Le Blanc; Lily HP Nguyen (Canadian Medical Education Journal)
Background: Websites that facilitate communication between patients regarding their experiences with individual physicians are now relatively commonplace. Given patient-generated ratings are publicly available, physicians could use these to access rarely available patient feedback. We explored the content of reviews associated with low physician ratings and consider the potential benefits and consequences of relying on this form of freely available data to support individual life-long learning.